Relationship between Obesity and Location of Residence with The Incidence of Fibroadenoma Mammae - Povitasari, P; Kurniati, Yuni Prastyo; Lestari, Nining; Mahmudah, Nur (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Fibroadenoma mammae (FAM) is a common benign breast tumor predominantly affecting young women. While obesity and location of residence are thought to influence the risk of FAM, evidence remains inconclusive. The aim to analyze the relationship between obesity, location of residence, and the incidence of FAM in Central Java, Indonesia. Methodology: This observational analytical study employed a case-control design using retrospective medical record data. The study included patients with breast tumors who underwent surgery and histopathological examination. Patients were categorized into the FAM group (cases) and non-FAM group (controls). Data on body mass index (BMI) and location of residence (urban or rural) were analyzed to determine their relationship with FAM. Results: The study revealed that FAM patients had a significantly younger median age compared to non-FAM patients (30 vs. 36 years; p = 0.015). Obesity was significantly less common in FAM patients than non-FAM patients (p = 0.001), with obese individuals having a 0.2 times lower risk of developing FAM (OR = 0.2). There was no significant association between location of residence and FAM incidence (p = 1.000; OR = 1.0). Applications/Originality/Value: There is a relationship between obesity status and the incidence of FAM. Obese women have a 0.2 times lower risk of experiencing FAM than non-obese study subjects, it can be considered that obesity is a protective factor against the occurrence of FAM. There is no relationship between location of residence and the incidence of FAM.